(untitled) (Journal of Asian Development Studies, 2026)
Consumer environmental consciousness is driving a shift towards eco-friendly consumption. Understanding the attitude of male consumers in this shift is of paramount importance, but receives little consideration. Hence, this research aims to assess the factors that affect male consumers’ purchase intentions of green cosmetics. Building on the theoretical foundations of the Theory of Planned Behaviour, it focuses on the key drivers such as perceived environmental benefits, price sensitivity, product effectiveness, subjective norms, and purchase convenience. The data were collected through a cross-sectional survey of male consumers in a large city, using a purposive sampling technique. The analysis is conducted using SmartPLS to assess reliability, validity, and model fit. Findings suggest that significant determinants of green cosmetics purchase intentions are consumer attitude and perceived behavioural control. Positive attitudes toward product efficacy and environmental benefits are strong motivators to purchase, along with social determinants such as subjective norms that reinforce consumer behaviour. Interestingly, the price sensitivity was observed to be less of an obstacle when bridged with the positive attitudes. Perceived convenience, such as information and accessibility, significantly contributes to green intention. The findings provide deeper insights into male consumer behaviour in the sustainable cosmetics market, offering implications for businesses seeking to tailor their strategies to penetrate and achieve broader sustainability goals.